SALICYLIC ACID ALTERS ANTIOXIDANT AND PHENOLICS METABOLISM IN CATHARANTHUS ROSEUS GROWN UNDER SALINITY STRESS - Misra, Neelam; Misra, Rahul; Ajiboye, Mariam; Yusuf, Kafayat; Yusuf, Lateefat (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Salicylic acid (SA) acts as a potential non-enzymatic antioxidant and a plant growth regulator, which plays a major role in regulating various plant physiological mechanisms. The effects of salicylic acid (SA; 0.05 mM) on physiological parameters, antioxidative capacity and phenolic metabolism, lignin, alkaloid accumulation in salt stressed Catharanthus roseus were investigated. Materials and Methods: Catharanthus roseus seeds were grown for two months in a glass house at 27–300C in sunlight, and then divided into four different groups and transplanted with each group with the following solutions for one month: group I (non-saline control), group II, 100 mM NaCl, group III, 0.05 mM SA, group IV, 100 mM NaCl+0.05 mM SA and to determine the physiological parameters (DW, FW, WC), chlorophyll contents, carotenoid contents, lipid peroxidation, phenolics, lignin, alkaloid and enzymatic assays in each leaf pairs and roots.Results: SA exhibited growth-promoting property, which correlated with the increase of dry weight, water content, photosynthetic pigments and soluble proteins. SA has additive effect on the significant increase in phenylalanine ammonia-lyase (PAL) activity, which is followed by an increase in total soluble phenolics and lignin contents in all leaf pairs and root of C. roseus. SA enhances malondialdehyde content in all leaf pairs and root. The antioxidant enzymes (catalase, glutathione reductase, glutathione-S-tranferase, superoxide dismutase, peroxidase) as well as alkaloid accumulation increased in all treatments over that of non-saline control but the magnitude of increase was found more in root. Further, the magnitude of increase of alkaloid accumulation was significantly higher in 100 mM NaCl, but highly significant was found in presence of 0.05 mM SA and intermediate in presence of both 0.05 mM SA+100 mM NaCl. Conclusion: We concluded that applied SA to salt stress, antioxidant and phenolic metabolism, and alkaloid accumulation were significantly altered and the extent of alteration varied between the SA and salt stress.